How long do pathogens persist and survive in water? A systematic review - Sosah, Famous K.; Odoom, Alex; Anim-Baidoo, Isaac; Donkor, Eric S. (Frontiers in Microbiology, 2025)
BackgroundWater is an important vehicle for transmitting pathogens that can cause waterborne diseases. Depending on environmental conditions, pathogenic microorganisms present in water can survive and persist for varying durations. A systematic understanding of pathogen survival and persistence under diverse environmental conditions is important for assessing water safety and guiding treatment requirements.MethodsA systematic search of PubMed, Web of Science, Google Scholar, and Scopus databases was conducted to identify studies published from January 1, 1990, to July 17, 2024. Studies were included and analysed if they provided quantitative data on the survival or persistence of bacteria, viruses, parasites, or fungi in different water sources, under varying environmental conditions such as temperature and pH. The PRISMA guidelines were followed, and the risk of bias in each study was evaluated using the Cochrane ROB2 tool.ResultsOf 2,048 initial records, 58 studies met inclusion criteria. Bacteria were the most studied group, with a mean survival of 28 days and persistence up to 621 days, especially at lower temperatures and in freshwater. E. coli O157:H7 and Salmonella spp. were the most studied bacteria, persisting for weeks to months in both freshwater and biofilms. Viruses averaged 22 days of survival but could persist up to 1,095 days; Human Adenovirus and Porcine epidemic diarrhea virus were the most frequently studied viral pathogens, while Human Norovirus survived over 70 days in surface water at 37°C. Viral viability decreased significantly at extreme pH levels. Parasites/protozoans, such as Cryptosporidium parvum and Giardia lamblia only showed survival duration, averaged 30 days survival, enduring extreme conditions and often benefiting from biofilm association. Fungi, though less studied, are emerging waterborne pathogens, with Candida auris surviving up to 30 days in water. Lower temperatures, neutral to slightly alkaline pH, and biofilms significantly enhanced pathogen persistence, even in treated water systems.ConclusionPathogenic microorganisms can survive and persist in diverse water environments for extended periods, posing ongoing risks for waterborne disease transmission and highlighting limitations in current water treatment strategies. Strengthening surveillance and disinfection protocols, prioritizing biofilm management strategies, and predictive modeling to enhance waterborne disease prevention and inform public health policies globally.